Actualization of Pancasila in The Implementation of Ethical Democracy in The Global Era - Nufikha Ulfah; Arofah Minasari; Yayuk Hidayah (Metafora: Education, Social Sciences and Humanities Journal, 2021)
As a value system, Pancasila provides a fundamental basis in the life of the community, nation, and state. The essence of the fourth principle of Pancasila is about democracy which is based on wisdom that is rooted in the moral principle of humanity and divinity. Therefore, according to the Pancasila view, democracy must be based on religious moral originating from God, justice and civilization. Nowadays, by seeing the application of democracy in Indonesia still has many problems, likes freedom as a symbol of democracy is not balanced with its quality, resulting in behavior that is contrary to democracy. Although freedom is guaranteed in the Constitution, oppression, discrimination, marginalization still occurs. Democracy does not only require laws, regulations, and institutions capable of enforcing it, but also democratic attitudes, namely the willingness to build a compromise with the awareness that a person cannot realize all that is desired (a combination of individual awareness and group awareness). True democracy requires good citizens. Therefore, democratic education that integrated through Citizenship Education is absolutely necessary with the aim of preparing citizens who are able to act with democratic ethics.